In vitro study of electron beam deposited calcium phosphate coating in simulated body fluid - Abd Shukor, Mohd Hamdi; Ide-Ektessabi, A.; Toque, J.A. (Materials Research Society, 2007)
Calcium phosphate coatings prepared using the technique of electron beam deposition were immersed in a simulated body fluid for different periods of time to determine their response in vitro. The amorphous as-deposited coatings dissolved completely after a few days of immersion. After annealing in air at 700 degrees C, the dissolution of a small amount of amorphous phase in the crystalline coatings promotes the precipitation of bonelike apatite on the recessed regions by increasing the local supersaturation of calcium and phosphate ions. Formation of apatite was confirmed by the x-ray diffraction peaks at (200), (211), and (203) planes which grew after immersion in simulated body fluid. Fourier transform infrared results conformed to this with the increase in intensity of the absorption band at 1450 cm(-1), signifying the increase in carbonate content. Scanning electron microscopy results showed spherical-shaped apatite nucleated on dissolved surface after 8 days of immersion. Sixteen days after immersion, almost 80 of the surface area was covered with apatite formation and grew to coalesce between neighboring particles forming an integrated platelike layer after 28 days. No obvious detachment between the grown layer and the underlying coating was observed.